Faisal Hossain Receives 2012 Charles S. Falkenberg Award: Citation. (15th January 2013) - Anagnostou, Emmanouil; Borga, Marco; Mahbubur Rahman, S. M.; Shum, C. K.
Abstract : Faisal Hossain received the 2012 Charles S. Falkenberg Award at the AGU Fall Meeting Honors Ceremony, held on 5 December 2012 in San Francisco, Calif. The award honors a "scientist under 45 years of age who has contributed to the quality of life, economic opportunities, and stewardship of the planet through the use of Earth science information and to the public awareness of the importance of understanding our planet.